Influence of Types Anti-Fungal Admixtures on the Concrete Mix - Atwan, Dalia Shakir (Nahrain University College of Engineering Journal, 2017)
In recent years, the antifungal concrete is developed by using several materials as admixtures. In this present study, the antifungal activity of concrete was evaluated against specie of fungi; Aspergillus niger which can be easily discovered in the interiors and exteriors of buildings by using two types of organic antifungal agents which are known commercially as Bleach and Savlon. Besides, the investigations also extends to evaluated the effect of these agents on the some basic properties of concrete produced such as:slump, compressive strength and absorption tests. Generally the results show that the all concrete mixes produced with different concentrations (0.5-2 % by weight of cement) for agents exhibited inhibitor effect for growth that fungi with varying degrees. Furthermore, most properties of activated concretes with antifungal agents demonstrate noticed decrease compared with properties of reference concrete.